Penerapan Model Pembelajaran M-APOS untuk Meningkatkan Kemampuan Pemahaman Konsep Matematis - Rahmi Putri; Mukhaiyar Mukhaiyar; Azwar Ananda (Jurnal Ilmiah Pendidikan Matematika Al Qalasadi, 2022)
This study aims to determine the improvement of students' ability to understand mathematical concepts through the application of the Modification-, Action, Process, Object, and Schema (M-APOS) learning model. The type of research conducted is quantitative research with a quasi-experimental method. This research uses a research design of The Randomized Pre-test Post-test Control Group Design. The population in this study was all class VIII at MTsN 2 Kerinci in the 2018/2019 school year. Through random sampling, it was obtained that class VIII C as the control group to be taught conventionally and class VIII A as the experimental group to which M-APOS learning would be applied, these two classes consisted of 26 students. The results of this study indicate that the hypothesis test I proved that the Modification – action, process, object, and schema (M-APOS) learning model can improve students' ability to understand mathematical concepts in relation and function material for class VIII MTsN 2 Kerinci. While the results of the hypothesis test II obtained the ability to understand students' mathematical concepts with the application of the learning model (M-APOS) is better than the ability to understand students' mathematical concepts with conventional learning. Keywords: Concept Understanding Ability, Modification Learning Model – action, process, object, and schema (M-APOS), Experiment Class and Conventional Class